Hubungan Pola Asuh Ibu Balita dengan Kejadian Stunting di Puskesmas Pangkalan Kabupaten Lima Puluh Kota - Nur Alam Fajar; Chairil Anwar; Nolly Julfery (Universitas Batanghari Jambi, 2023)
Stunting is one of the targets of the Sustainable Development Goals (SDGs) which includes the 2nd goal of sustainable development, namely ending hunger, achieving food security, improving nutrition, and proclaiming sustainable agriculture. The purpose of this study was to analyze the relationship between mother-to-child parenting and the incidence of stunting at the Pangkalan Health Center, Fifty Cities District. This research is an analytic observational and descriptive analytic study with a cross-sectional study design. A sample of 88 mothers with stunted toddlers aged 8-60 months in the working area of the primary health center was taken by purposive sampling. Data collected regarding exclusive breastfeeding habits, feeding habits, hygiene habits, and health habits of mothers and toddlers obtained through direct interviews and questionnaires, and the incidence of stunting in toddlers obtained from measuring the toddler's height and weighing the toddler's weight. Data analysis to see the relationship between variables using the Chi-Square test. The results showed that 87.5% of the incidence of stunting in toddlers. There is a significant relationship between exclusive breastfeeding (p-value = 0.003), feeding (p-value = 0.037), hygiene practices (p-value = 0.042), and practice maternal and toddler health (p-value = 0.047) with the incidence of toddler stunting. The results of the logistic regression test showed that the most dominant variable in this study was exclusive breastfeeding.